Balanced Scorecard (BSC) implementation towards value creaction within a Malaysian Government-linked Company (GLC) / Norlaila Md Zin - Md Zin, Norlaila (Institute of Graduate Studies, UiTM, 2018)
It has been noted that businesses seek to increase capability and improve performance using Balanced Scorecard. From a performance viewpoint, Balanced Scorecard has been widely advocated as a potential competitive management tool that contributes to firm performance, particularly in the Government-linked Company, the focus of this study. This is important because Government-linked Companies play a vital role in the Malaysian economic development and constantly responding to the changes following the environmental forces of globalization. A possible opportunity for advancement of Balanced Scorecard as a competitive management innovation tool is the potential contribution to create value for companies. Furthermore, the shift towards comprehensive value creation within BSC adoption and implementation is consistent with the recent developments in management accounting. However, studies which examine Balanced Scorecard adoption and implementation have often resulted in inconclusive results. Furthermore, it has been acknowledged that the successful adoption and implementation depends on the factors that facilitate or hinders (critical success factors). Yet, the studies are mainly conducted in the developed countries with little emphasis on developing countries. Little attempt also has been made in the literature to examine the diffusion of Balanced Scorecard at organisational level within Malaysian Government-linked Companies. In addition, the cumulative knowledge on the motives of adoption and implementation of innovations from the theoretical and practical perspectives is still lacking. These issues are examined using an exploratory and explanatory case study method on a Government-linked company in Malaysia to provide a holistic view of the adoption and implementation of BSC…